Animals as Online Resources for Human Storytelling. Between Exploitation and Anthrozoological Empowerment - Iris Bauer (Czytanie Literatury)
The paper deals with online representations of animals and examines the extent to which the digital age, with its media and specific characteristics, influences the representation of animals. The text introduces the basic questions of human animal studies, using Randy Malamud’s virtual animal concept to scrutinise online representations of animals in social media. Based on Spivak’s concept of subalternity, online-animals are discussed as subaltern representations, that are instrumentalised in human story telling: as an economic resource, as a projection surface for individual life writing and identity creation and as a means of social networking. Yet social media are also discussed as a space in which anthrozoological empowerment can take place. Based on Kari Weil’s concept of the contact zone, the virtual animal is discussed as a space of possibilities for a posthuman language that, with the help of digital possibilities of representation, unsettles anthropocentric hegemony.